DEVELOPMENT OF THE BABA CAVE TOURISM OBJECT IN BATU GADANG VILLAGE, LUBUK KILANGAN DISTRICT, PADANG CITY - Muhammad Riyadh Fatwa; Sri Mariya (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This research aims to determine the development of the Baba Cave tourist attraction in Batu Gadang Village, Lubuk Kilangan District, Padang City and also to find out the obstacles in developing the Baba Cave tourist attraction in Batu Gadang Village, Lubuk Kilangan District, Padang City. This type of research is qualitative research with data collection techniques using observation and interviews. The sampling technique uses snowball sampling. Data analysis techniques use miles and Huberman analysis to analyze attractiveness, and site analysis for planning. The results of this research are that the development of the Baba Cave tourist attraction in Batu Gadang sub-district requires planning for the creation of facilities and infrastructure in developing the tourist attraction. Due to the lack of facilities, the focus is on creating facilities and infrastructure in the form of facilities that are really needed for the development stage of tourist attractions. Then the obstacle is related to the development of tourist attractions in Baba's cave regarding environmental problems, namely the lack of human resources to manage the surrounding natural areas. The active role of the community is expected to support the development that will be carried out to manage tourist attractions.